2011
DOI: 10.1177/0300985811406885
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Equine Parkinsonism: An Immunohistochemical Study of 10 Horses With Nigropallidal Encephalomalacia

Abstract: Chronic ingestion of yellow star thistle (Centaurea solstitialis) or Russian knapweed (Acroptilon repens) causes nigropallidal encephalomalacia (NPE) in horses with an abrupt onset of neurologic signs characterized by dystonia of lips and tongue, inability to prehend food, depression, and locomotor deficits. The objectives of this study were to reexamine the pathologic alterations of NPE and to conduct an immunohistochemistry study using antibodies to tyrosine hydroxylase and a-synuclein, to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Roy et al isolated and characterised two potent neuroexcitotoxic compounds—aspartic acid and glutamic acids—and found other neurotoxic compounds in their extracts, requiring further attention 18. Chang et al used antibodies to tyrosine hydroxylase and α-synuclein in an immunohistochemistry study19 and confirmed that lesions occurred within the substantia nigra pars reticularis and in the rostral globus pallidus, thus confirming Cordy's original description. There were no abnormal Lewy body-like cytoplasmic inclusions.…”
Section: Further Workmentioning
confidence: 67%
“…Roy et al isolated and characterised two potent neuroexcitotoxic compounds—aspartic acid and glutamic acids—and found other neurotoxic compounds in their extracts, requiring further attention 18. Chang et al used antibodies to tyrosine hydroxylase and α-synuclein in an immunohistochemistry study19 and confirmed that lesions occurred within the substantia nigra pars reticularis and in the rostral globus pallidus, thus confirming Cordy's original description. There were no abnormal Lewy body-like cytoplasmic inclusions.…”
Section: Further Workmentioning
confidence: 67%
“…These findings indicate that equine NPE can serve as a large animal model of environmentally acquired toxic Parkinsonism. The clinical phenotype is directly attributable to lesions in the globus pallidus and substantia nigra pars reticulata rather than to the destruction of dopaminergic neurons [58].…”
Section: Behavioral Alterations: Stereotipiesmentioning
confidence: 99%
“…It was suggested that ENPE may serve as a large animal model of environmentally acquired toxic parkinsonism, with clinical phenotype directly attributable to lesions in globus pallidus and substantia nigra pars reticulata rather than to the destruction of dopaminergic neurons. 9 Diagnosis of ENPE is often confirmed by postmortem examination of the brain; however, MRI can be used to detect lesions in affected areas of the brain antemortem.…”
Section: Equine Nigropallidal Encephalomalaciamentioning
confidence: 99%